Language use and tourism in Yogyakarta; The linguistic landscape of Malioboro - Tjung, Yassir Nasanius; Wijayanti, Sri Hapsari; Suwartono, Christiany; da Silva, Anna Marietta (UI Scholars Hub, 2021)
The present study provides a depiction of Malioboro through language presentation, language preference and sign informativeness. Seven hundred and twenty-nine public signs were examined and analyzed. Analysis was limited to words. A survey on language preference and sign informativeness, clarity and visibility to both local and foreign visitors also conducted. Findings show the dominance of Indonesian language in Malioboro linguistic landscape; 73% of the signs were in Indonesian and all non-commercial signs used Indonesian. Only 15% of the entire signs use English and less than 5% of the signs contain Javanese script or Romanized Javanese. Mainly targeting Indonesian speakers, the LL of Malioboro presents an exclusiveness and reflects a language policy implementation. The survey shows an indication of having both Indonesian and English in Commercial, Regulatory, and Infrastructure signs, most of which are informative.